Analisis Kualitas Produksi Batu Bata Dengan Pendekatan Berbasis Diagram Pareto Dan Diagram Fishbone - Selviani, Windi; Mahariani, Yeni Roha (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Universitas Qomaruddin, Gresik, Indonesia, 2025)
Brick production in traditional micro, small, and medium enterprises (MSMEs) often exhibits inconsistent quality. This condition leads to various physical defects in the final products and reduces the proportion of saleable bricks. The main problems identified include broken, burnt, and cracked defects. This study aims to analyze the dominant types of defects, identify their root causes, and formulate practical improvement actions applicable to MSMEs. The research employs a Pareto diagram to determine defect priorities, a fishbone diagram to identify root causes, and the 5W+1H analysis as a systematic tool for developing improvement actions. The Pareto analysis indicates that broken defects are the most dominant, accounting for 42% of total defects, followed by burnt defects at 38% and cracked defects at 20%. The fishbone analysis reveals that defects are primarily caused by unbalanced raw material composition, the absence of firing temperature measuring instruments, and uncontrolled drying processes. The 5W+1H analysis proposes improvement actions, including the use of firing temperature measurement tools, raw material measuring instruments, and the reorganization of the drying process to ensure greater stability and consistency. The study concludes that simple but well-controlled interventions in material mixing, firing, and drying stages can effectively reduce defect rates and improve the overall quality of brick production in MSMEs.